An atrionodal and nodo-Hisian gap phenomenon. Issue 11 (November 1975) - Pop, T; Fleischmann, D; de Bakker, J M; Effert, S
Abstract : Two cases of the gap phenomenon are presented. The first was an example of a gap between the atrium and the AV node. In the second the gap was at the nodo-Hisian junction. At a critical H1H2 interval splitting of the premature His potential occurred. A decrease of the H1H2 interval led to the disappearance of the distal H2 potential and to atrioventricular block. But at even shorter coupling intervals the H1H2 interval lengthened suddenly with resumption of the AV conduction. These observations provide further evidence that the gap phenomenon has a wider spectrum than was previously thought.